Quinazoline-containing Hydrazydes of Dicarboxylic Acids and Products of Their Structural Modification – A Novel Class of Anti-inflammatory Agents - Krasovska, N.; Stavytskyi, V.; Nosulenko, I.; Karpenko, O.; Voskoboynik, O.; Kovalenko, S. I.; Ставицький, Віктор Валерійович; Носуленко, Інна Степанівна; Воскобойнік, Олексій Юрійович; Коваленко, Сергій Іванович (My University, 2021)
The synthesis of hydrazides formed by quinazolin-4(3H)-ylidenehydrazine and dicarboxylic acids, as well as their further modification are described in the present manuscript. It was shown that above-mentioned hydrazides may be obtained via acylation of initial quinazolin-4(3H)-ylidenehydrazine by corresponding acylhalides, cyclic anhydrides and imidazolides of dicarboxylic acids monoesters. Obtained hydrazides were converted into [1,2,4]triazolo[1,5-с]quinazolines that were used as initial compounds for chemical modification aimed to the introduction of amide fragment to the molecule. The IR, 1H NMR and chromato-mass spectral data of obtained compounds were studied and discussed. Obtained substances were studied for anti-inflammatory activity using carrageenan-induced paw inflammation model. Amides of ([1,2,4]triazolo[1,5-с]quinazoline-2-yl)alkyl carboxylic acids were detected as promising class of anti-inflammatory agents for further purposeful synthesis and profound study of anti-inflammatory activity.
Keywords: [1,2,4]triazolo[1,5-с]quinazolines; quinazolines; anti-inflammatory activity